MENINGKATKAN MOTIVASI BERPRESTASI, KEMANDIRIAN, DAN PENYESUAIAN DIRI KARYAWAN - Salmah Lilik (PAEDAGOGIA, 2008)
The objectives of this research are to find out: (1) the correlation between the achievement motivation and the work achievement of the UNS employees; (2) the autonomy of the UNS employees in their work; (3) the adaptation of UNS employees and their work achievement. The research used descriptive correlational method. The technique of collecting data was questionnaire. The data analysis was done by using descriptive statistics and correlational technique. The result of the research shows that there is no correlation between: (1) autonomy and working performance; (2) achievement motivation and working performance; (3) adaptation and working performance; (4) achievement motivation and autonomy; (5) achievement motivation and adaptation but there is correlation between adaptation and autonomy of the UNS employees